Practical limitation on operation of nonlinear parity-time Bragg gratings - Phang, Sendy; Vukovic, Ana; Susanto, Hadi; Benson, Trevor M.; Sewell, Phillip (2014)
The paper analyses the operation of PT Bragg gratings when the dielectric material is considered to be both dispersive and nonlinear and gain and loss are saturable. The paper demonstrates the application of the nonlinear PT Bragg Grating as an optical logic gate and an optical switch.